Impact of an Interactive On-line Tool on Therapeutic Decision-Making for Patients with Advanced Non–Small-Cell Lung Cancer. Issue 10 (October 2015) - Chow, Helen; Edelman, Martin J.; Giaccone, Giuiseppe; Ramalingam, Suresh S.; Quill, Timothy A.; Bowser, Andrew D.; Mortimer, Jim; Guerra, Wilma; Beckett, Laurel A.; West, Howard L; Lara, Primo N.; Gandara, David R.
<x xml:space="preserve">Abstract</x> Background: Treatment guidelines provide recommendations but cannot account for the wide variability in patient-tumor characteristics in individual patients. We developed an on-line interactive decision tool to provide expert recommendations for specific patient scenarios in the first-line and maintenance settings for advanced non–small-cell lung cancer. We sought to determine how providing expert feedback would influence clinical decision-making. Method: Five lung cancer experts selected treatment for 96 different patient cases based on patient and/or tumor-specific features. These data were used to develop an on-line decision tool. Participant physicians entered variables for their patient scenario with treatment choices, and then received expert treatment recommendations for that scenario. To determine the impact on decision-making, users were asked whether the expert feedback impacted their original plan. Results: A total of 442 individual physicians, of which 88% were from outside the United States, entered 653 cases, with report on impact in 389 cases. Expert feedback affected treatment choice in 73% of cases (23% changed and 50% confirmed decisions). For cases with epidermal growth factor receptor (EGFR) mutation or anaplastic lymphoma kinase (ALK) fusion, all experts selected targeted therapy whereas 51% and 58% of participants did not. Greater variability was seen between experts and participants for cases involving EGFR or ALK wild-type tumors. Participants were 2.5-fold more likely to change to expert recommended therapy for ALK fusions than for EGFR mutations (p = 0.017). Conclusion: This online tool for treatment decision-making resulted in a positive influence on clinician's decisions. This approach offers opportunities for improving quality of care and meets an educational need in application of new therapeutic paradigms.